Dust in galaxies throughout cosmic time - Rowlands, Kate (2013)
One of the most fundamental observational probes of galaxy evolution is determining the build-up of stellar mass. However, around half of all energy ever emitted from galaxies has been absorbed and reprocessed by dust, which is an end-product of stellar evolution. In order to obtain a more complete understanding of galaxy evolution, sensitive observations in the far-infrared and submillimetre are required where the dust emission peaks. Previous surveys have found galaxies were significantly dustier at earlier times, but the cause of this evolution, and the origin of the dust, are hotly debated topics in astrophysics. With the Herschel Space Observatory, a complete census of the dusty galaxy population has now recently been obtained. In this thesis I investigate the properties of the diverse dusty galaxy population via a panchromatic approach, utilising data from the UV to the submillimetre to study galaxy evolution.